Association between antidepressant prescribing and suicide in Australia, 1991-2000: trend analysis - Hall, Wayne D (BMJ Publishing Group Ltd, 2003)
OBJECTIVE: To examine the association between trends in antidepressant prescribing and suicide rates in Australia for 1991-2000. DESIGN: Analysis of databases of suicide and rates of antidepressant prescribing according to age and sex. SETTING: Australian Bureau of Statistics data, sales data from the Australian pharmaceutical industry, prescribing data in general practice. SUBJECTS: Men and women aged 15 years and over in 10 year age groups. MAIN OUTCOME MEASURES: Trends in suicide rates and trends in antidepressant prescribing. Association measured by Spearman's rank correlations. RESULTS: While overall national rates of suicide did not fall significantly, incidence decreased in older men and women and increased in younger adults. In both men (r(s)=−0.91; P<0.01) and women (r(s)=−0.76; P<0.05) the higher the exposure to antidepressants the larger the decline in rate of suicide. CONCLUSIONS: Changes in suicide rates and exposure to antidepressants in Australia for 1991-2000 are significantly associated. This effect is most apparent in older age groups, in which rates of suicide decreased substantially in association with exposure to antidepressants. The increase in antidepressant prescribing may be a proxy marker for improved overall management of depression. If so, increased prescribing of selective serotonin reuptake inhibitors in general practice may have produced a quantifiable benefit in population mental health.